Answer:
6 − 4 x = 6 x − 8 x − 2 Since x
is on the right side of the equation, switch the sides so it is on the left side of the equation.
6 x − 8 x − 2 = 6− 4 x Subtract 8 x from 6 x . − 2 x − 2 = 6 − 4 x
Move all terms containing x
to the left side of the equation.
Tap for fewer steps...
Add 4 x
to both sides of the equation.
− 2 x − 2 + 4 x = 6 Add − 2 x and 4 x . 2 x − 2 = 6
Move all terms not containing
x to the right side of the equation.
Tap for fewer steps...
Add 2
to both sides of the equation.
2 x = 6 + 2 Add 6 and 2 . 2 x = 8
Divide each term by
2 and simplify.
Tap for fewer steps...
Divide each term in
2 x = 8 by 2 . 2 x 2 = 8 2 Cancel the common factor of
2 . Tap for more steps...
x = 8 2 Divide 8 by 2 .
x = 4